Between imagination and representation. About the aesthetics of the spectacle and the imaginary potency of existence - González Araneda, Sergio (Escritura e Imagen, 2021)
Based on the philosophical reflections of Guy Debord, we attempt to rethink the intersection between spectacle and metaphysics of the image in a context of secular anarchic capitalism. For this, we take as a guide of analysis the genesis and constitution of an aesthetics of the spectacle that deploys and signifies the world as a simple representation of the real. In a second moment, and with the presence of Benjamin, Agamben and Heidegger, the latency of capitalism as a religion will become clear, within the constellation of an all-encompassing and technified capitalism. Finally, we will show the modality in which the metaphysics of the image, administered by a given technique of operativity, becomes a fundamental, representative and static order of meaning. From this context, we propose a theoretical and practical possibility to disarticulate the representational (and representative) spectacle from what we call the imaginative power of existence.
Keywords: Agamben; Debord; spectacle; imagination; metaphysics of image